Analysis of Participatory Approaches of Community-Based Sustainable Marine Protected Area Management Groups - Gusman, Alyandra; Supriyadi, Supriyadi (CV. Publikasi Indonesia, 2024)
This study was conducted to see the role of community participation in the management of community-based marine protected areas. In addition, this study also shows the impact of conservation area management on improving community welfare and improving the quality of the environment. The research design used is a mixed method which is a combination of qualitative and quantitative analysis. Qualitative analysis uses in-depth interview methods with resource persons, while quantitative analysis uses the one-sample test method to test respondents' perceptions related to research variables. The research sample consisted of the Head of the Management Group, Village Head, Traditional Head, Religious Leaders, and Community Member Representatives in Roon District, Teluk Wondama Regency, West Papua, Indonesia. Research findings show that the role of the community in the management of conservation areas is very high, this can be seen from the supervisors of conservation area management groups consisting of Government, Religious, and Social groups. In addition, active participation from the community around the conservation area is also the key to the success of good area management. The findings of one sample test showed, that 1) The participation of members of the Marine Protected Area group has been classified as high, 2) Sasi culture has been proven to affect the income level of the community, 3) Member participation has been proven to be active in decision making, 4) The existence of Sasi has been proven to increase the sustainability of natural resources, 5) Proven to successfully contribute to the achievement of SDG number 14.